Sheltered employment in Spain: challenges for a new model of special employment centres - Ortega Camarero, Maria Teresa (HUMAN REVIEW. International Humanities Review / Revista Internacional de Humanidades, 2023)
Special Employment Centres create employment for people with disabilities (PWD). It addresses their situation after the United Nations International Convention on the Rights of Persons with Disabilities. The conclusions corroborate their contribution to the social economy and provide challenges for a questioned model, which must address aspects such as: the differentiation of social and private initiative companies; wage improvement; the special employment relationship; sectoral agreements; the professionalisation of management and support teams; the training of their staff and the implementation of measures to guarantee their future viability.